Bicoronal and metopic craniosynostosis in association with a de novo unbalanced t(2;7) chromosomal translocation. Issue 1 (24th October 2016) - O'Byrne, James J.; Ryan, Helen; Murray, Dylan J.; Regan, Regina; Betts, David R.; Murphy, Nuala; Casey, Jillian P.; Lynch, Sally A.
Abstract : We report the case of a developmentally appropriate infant male with a de novo unbalanced chromosome translocation involving bands 2q32.1 and 7p21.3. The child was noted to have metopic and bicoronal craniosynostosis with closely spaced eyes, turricephaly, and flattening of the forehead. © 2016 Wiley Periodicals, Inc.